2021
DOI: 10.1242/dmm.049044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the oncogenomic landscape of canine and feline hemangiosarcoma shows novel parallels with human angiosarcoma

Abstract: Angiosarcoma (AS) is a highly aggressive tumor of blood and lymphatic vessels in humans that carries a poor prognosis. The rarity of AS, together with its heterogeneous nature, and locations (skin, breast, visceral organs and deep soft tissues), makes understanding the pathogenesis of AS challenging. Dogs and cats spontaneously develop hemangiosarcoma (HSA), an aggressive tumor that shares many histopathological and clinical similarities to AS. To investigate the genetic suitability of spontaneously occurring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 71 publications
2
49
0
Order By: Relevance
“…Such studies have identified recurrent putative driver mutations in genes such as TP53, KDR, PIK3CA, RAS, ARID1A, POT1, PTPRB, and PLCG1. Similar mutations have been reported recently in studies of canine hemangiosarcomas where TP53, PIK3CA, NRAS, PTEN, and PLCG1 are the most commonly mutated genes [11][12][13][14]. These studies have begun to reveal common aberrations among specific anatomic locations and subtypes of tumors.…”
Section: Introductionsupporting
confidence: 76%
“…Such studies have identified recurrent putative driver mutations in genes such as TP53, KDR, PIK3CA, RAS, ARID1A, POT1, PTPRB, and PLCG1. Similar mutations have been reported recently in studies of canine hemangiosarcomas where TP53, PIK3CA, NRAS, PTEN, and PLCG1 are the most commonly mutated genes [11][12][13][14]. These studies have begun to reveal common aberrations among specific anatomic locations and subtypes of tumors.…”
Section: Introductionsupporting
confidence: 76%
“…Human AS accounts for only 1% of all human malignant tumors, making research difficult. However, canine HSA occurs 5-20 times more frequently than human AS, accounting for approximately 7% of canine malignancies [17,40]. The histopathological features of canine HSA are similar to those of human AS [40].…”
Section: Introductionmentioning
confidence: 95%
“…However, canine HSA occurs 5-20 times more frequently than human AS, accounting for approximately 7% of canine malignancies [17,40]. The histopathological features of canine HSA are similar to those of human AS [40]. Furthermore, both human AS and canine HSA exhibit certain mutations in several genes, such as TP53, phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit α, and lowdensity lipoprotein receptor-related protein 1 B [11,28].…”
Section: Introductionmentioning
confidence: 99%
“…There is only one study that has looked at the genetics of HSA in cats. A targeted sequencing approach was taken to look at ~1000 cancer-associated genes in paired tumour-normal samples of 13 feline cutaneous HSA cases [ 120 ]. The most recurrently mutated genes in the HSA samples were TP53 (6/13, 46% cases) and NOTCH1 (2/13, 15% cases) [ 120 ].…”
Section: Haemangiosarcomamentioning
confidence: 99%
“…A targeted sequencing approach was taken to look at ~1000 cancer-associated genes in paired tumour-normal samples of 13 feline cutaneous HSA cases [ 120 ]. The most recurrently mutated genes in the HSA samples were TP53 (6/13, 46% cases) and NOTCH1 (2/13, 15% cases) [ 120 ]. It is interesting to note that in human HFNS AS, the most commonly mutated gene is TP53 (9/19 patients, 47% cases), with NOTCH1 also being frequently mutated (5/19 samples, 26% cases) [ 120 ].…”
Section: Haemangiosarcomamentioning
confidence: 99%